Driving under the influence of prescription opioids: Self-reported prevalence and association with collision risk in a large Canadian jurisdiction. (December 2018) - Wickens, Christine M.; Mann, Robert E.; Brands, Bruna; Ialomiteanu, Anca R.; Fischer, Benedikt; Watson, Tara Marie; Matheson, Justin; Stoduto, Gina; Rehm, Jürgen
Highlights: Examined driving under the influence of prescription opioids (DUIPO) in Ontario, Canada. Past-year prevalence of DUIPO among Ontario adults was 3.1%. After adjusting for other factors, DUIPO increased odds of a collision almost twofold. Implications for health and legislative policy and research needs are discussed. Abstract: Background: Motor vehicle collisions are an important contributor to prescription opioid use-related morbidity and mortality. The purpose of the current study was to estimate the prevalence of driving under the influence of prescription opioids (DUIPO) in Ontario, Canada, and to measure the association between this behaviour and the risk of a motor vehicle collision. Methods: Data were based on telephone interviews with 7857 respondents who reported having driven in the past year. Data were derived from the 2011–2016 cycles of the CAMH Monitor, an ongoing cross-sectional representative survey of adults aged 18 years and older. A binary logistic regression analysis of collision involvement in the previous 12 months was conducted and included demographic characteristics (sex, age, marital status, education, income, region), driving exposure, poor mental health, non-medical use of prescription opioids, and driving after use of alcohol. Results: The prevalence of past-year DUIPO was 3.1%. Controlling for demographic characteristics, driving exposure, and other risk factors, self-reported DUIPO significantly increased the odds of a collision (Adj OR  = 1.97; 95% CI 1.08, 3.60; p  = 0.026). Conclusion: Based on these findings, DUIPO is a notable road safety issue. Research focused on better understanding the impact of prescription opioids on driver behaviour, reducing the prevalence of DUIPO, and improving drug-impaired driving policy and interventions should be prioritized in public health strategies.